2020
DOI: 10.15560/16.3.685
|View full text |Cite
|
Sign up to set email alerts
|

Annotated list of anurans from the lateritic plateau of western India with notes on malformations

Abstract: Lateritic plateaus of India are geographically and ecologically complex plateaus that support endemic flora and fauna. However, despite their uniqueness they are termed as “wastelands”. The plateaus’ overall treeless structure makes them susceptible to developmental activities like infrastructure growth, waste dumping, and urbanization. This paper presents a list of anurans compiled from surveys carried out in the years between 2016 and 2018 in the town of Manipal, a predominant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We found that cashew plantations shelter 6 out of 9 understorey anurans in TCR and provide supplementary habitat for one threatened anuran species that was not found in a forest or forest edge, Pseudophilautus amboli . This bush frog has been reported from modified habitats and forests alike and is considered threatened due to anthropogenic activities throughout its extent (Biju, 2004; Hegde, 2012; Mudke et al, 2020). Cashew plantations had similar anuran abundance as observed in forest interiors.…”
Section: Discussionmentioning
confidence: 99%
“…We found that cashew plantations shelter 6 out of 9 understorey anurans in TCR and provide supplementary habitat for one threatened anuran species that was not found in a forest or forest edge, Pseudophilautus amboli . This bush frog has been reported from modified habitats and forests alike and is considered threatened due to anthropogenic activities throughout its extent (Biju, 2004; Hegde, 2012; Mudke et al, 2020). Cashew plantations had similar anuran abundance as observed in forest interiors.…”
Section: Discussionmentioning
confidence: 99%
“…Nuestro reporte suma una especie a la lista de anfibios de México con algún tipo de anomalía morfológica, y representa el primer caso de anomalía para una especie de la familia Microhylidae a nivel nacional. En otros países de la región tropical se han reportado diferentes anomalías en especies de la familia Microhylidae, como anoftalmia (Mudke et al, 2020), amelia (ausencia de extremidades; Pett et al, 2019), ectrodactilia y braquidactilia (Brouard & Smith, 2014). En anfibios con anomalías morfológicas se ha observado una reducción en la habilidad para cazar y reproducirse (Johnson et al, 2001).…”
unclassified
“…Dubois's leaping frog Indirana duboisi Dahanukar, Modak, Krutha, Nameer, Padhye, and Molur, 2016 was erected as a new species following taxonomic revisions of the Ranixalidae (Dahanukar et al, 2016;Garg & Biju, 2016). In 2019, the species was recorded for the first time from the laterite plateaus of Manipal (Karnataka State) that adjoin the Western Ghats (Mudke et al, 2020). The site where it was observed (13°20' 27.24" N 74°47' 13.56" E) is at an altitude of 80 m a.s.l.…”
mentioning
confidence: 99%